2007
DOI: 10.1111/j.1475-679x.2007.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Information, Disclosure, and the Cost of Capital

Abstract: In this paper we examine whether and how accounting information about a firm manifests in its cost of capital, despite the forces of diversification. We build a model that is consistent with the Capital Asset Pricing Model and explicitly allows for multiple securities whose cash flows are correlated. We demonstrate that the quality of accounting information can influence the cost of capital, both directly and indirectly. The direct effect occurs because higher quality disclosures affect the firm's assessed cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
694
4
26

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,871 publications
(832 citation statements)
references
References 58 publications
38
694
4
26
Order By: Relevance
“…Numerous advantages of providing high-quality information have been cited: FRQ reduces information risk and liquidity (Lambert et al, 2007), prevents managers from using discretionary powers for their own benefit and helps them make efficient investment decisions (Chen et al, 2010). Lambert et al (2007) obtained empirical evidence that the quality of accounting information can influence the cost of capital, both directly, by affecting market participants' perceptions about the distribution of future cash flows, and indirectly, by affecting real decisions that alter the distribution of future cash flows.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous advantages of providing high-quality information have been cited: FRQ reduces information risk and liquidity (Lambert et al, 2007), prevents managers from using discretionary powers for their own benefit and helps them make efficient investment decisions (Chen et al, 2010). Lambert et al (2007) obtained empirical evidence that the quality of accounting information can influence the cost of capital, both directly, by affecting market participants' perceptions about the distribution of future cash flows, and indirectly, by affecting real decisions that alter the distribution of future cash flows.…”
Section: Discussionmentioning
confidence: 99%
“…Lambert et al (2007) obtained empirical evidence that the quality of accounting information can influence the cost of capital, both directly, by affecting market participants' perceptions about the distribution of future cash flows, and indirectly, by affecting real decisions that alter the distribution of future cash flows. Chen et al (2010) found that FRQ positively affects the investment efficiency of private firms in emerging markets and this effect enhances bank financing and decreases incentives to minimise earnings for tax avoidance purposes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations